2012
DOI: 10.1044/1058-0360(2012/11-0007)
|View full text |Cite
|
Sign up to set email alerts
|

Tone Discrimination as a Window Into Acoustic Perceptual Deficits in Parkinson’s Disease

Abstract: Purpose Deficits in auditory perception compromise a range of linguistic processes in persons with Parkinson’s disease (PD), including speech perception and sensitivity to affective and linguistic prosody. An unanswered question is whether this deficit exists not only at the level of speech perception, but also at a more pervasive level of auditory perception. It is possible that PD produces a selective impairment in the perception of a salient acoustic feature such as frequency, amplitude, or duration. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 43 publications
2
35
1
Order By: Relevance
“…However, the most pronounced temporal auditory impairment in PD remains controversial. The results of the GIN test in our study revealed no difference between the non-PD and the PD groups, as it was observed in previous investigations that evaluated temporal perception 12,13 . On the other hand, worse detection, discrimination and naming of gaps have already been identified in individuals with PD 12,13 .…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…However, the most pronounced temporal auditory impairment in PD remains controversial. The results of the GIN test in our study revealed no difference between the non-PD and the PD groups, as it was observed in previous investigations that evaluated temporal perception 12,13 . On the other hand, worse detection, discrimination and naming of gaps have already been identified in individuals with PD 12,13 .…”
Section: Discussionsupporting
confidence: 84%
“…The results of the GIN test in our study revealed no difference between the non-PD and the PD groups, as it was observed in previous investigations that evaluated temporal perception 12,13 . On the other hand, worse detection, discrimination and naming of gaps have already been identified in individuals with PD 12,13 . It is believed that these findings are a reflection of tasks used that recruited greater cognitive expression, since they approached the indication of intervals by means of the comparison between listening conditions at different moments, also involving memorization, besides the perception of the interval itself.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Previous studies have identified other clinical markers currently used in movement disorders clinics or investigated in Parkinson disease research centers around the world, including hyperechogenicity of the substantia nigra using transcranial sonography [9], olfactory testing [10], acoustic analysis [11], and cerebrospinal fluid analysis [12]. Some of these tests, like optical coherence tomography or transcranial sonography, require specific expertise and equipment and may have suboptimal specificity.…”
mentioning
confidence: 99%